Ergonomic study on eye discomfort for using ump website homepage by applying Jakob Nielsen’s heuristics - Iza Nor Afinie, Mohd Samuri (2013)
UMP website is the official page to disseminate information, notification of academic and co-curricular activities involving either to students, staffs and lecturers. The usability of a user interface becomes extraordinary important and the development of the website should be in accordance with the specifications and the proper principles. Therefore, ergonomics awareness about eye discomfort is an important thing when developing a website. The purpose of an ergonomic study of eye discomfort is to raise the level of development of a website and will create awareness about the importance use of the appropriate colour, font and size when the implementation process. On awareness, the project is carried out with the objectives is to identify which part of user interface design of UMP website that extremely exposed to ergonomic eye discomfort and proposed alternatives for improvement. Method used for the data collection process is through questionnaires about existing UMP websites and involving 20 respondents including admin, staff and students for all faculties of UMP Gambang. Jakob Nielsen's heuristics principles that related to describe eye discomfort used as a technique to be applied in the development process of a website in order to gain the proper specification of implementation.